The role of international experience in business models of SMEs - evidence from software companies. (10th April 2015) - Sainio, Liisa–Maija; Saarenketo, Sami; Sengupta, Sanjit; Ahokangas, Petri; Laaksolahti, Mikko
This paper examines the role of international experience in value creation in business models in internationalising software SME's. While business models as such have been subject to extensive research their study in the context of international entrepreneurial firms has remained scant. The empirical part of the paper focuses on eight Finnish international entrepreneurial software companies. The findings suggest that business models of software companies incorporate many similarities. However, the degree of international experience seems to influence the companies' value creation and the way they organise their activities both upstream and downstream of their value chains. Moreover, as international experience grows the firms tend to outsource more of their core activities, affecting the business model design.